PARTICIPATION DECISION MAKING, PSYCHOLOGICAL EMPOWERMENT, JOB RELEVANT INFORMATION AND MANAGERIAL PERFORMANCE - Kala’Padang, Flaviana Iki; Daromes, Fransiskus Eduardus (Dinamika Akuntansi Keuangan dan Perbankan, 2023)
This study intends to investigate how psychological empowerment and job-relevant information are affected by participatory decision-making, as well as how this affects managerial performance. The self-determination theory and information processing theory served as the foundation for the research model. The study's participants included all of the Central Federation of Credit Union Cooperatives in Indonesia's managers of credit union cooperatives, according to a questionnaire. Path analysis and regression are used to process the data. The analysis of the data reveals that participatory decision-making significantly and favorably affects both psychological empowerment and job information. The impact of psychological empowerment and job-relevant information. on managerial performance is similar. Further research demonstrates that the association between participative decision-making and managerial performance is mediated by both psychological empowerment and job-relevant information.